SARS-CoV-2 and the role of orofecal transmission: a systematic review - Heneghan, CJ; Spencer, EA; Brassey, J; Plüddemann, A; Onakpoya, IJ; Evans, DH; Conly, JM; Jefferson, T (F1000Research, 2021)
Background: Modes of transmission of SARS-CoV-2 are of key public health importance. SARS-CoV-2 has been detected in the feces of some COVID-19 patients, suggesting the possibility that the virus could, in addition to droplet and fomite transmission, be transmitted via the orofecal route. Methods: This review is part of an Open Evidence Review on Transmission Dynamics of COVID-19. We conduct ongoing searches using WHO COVID-19 Database, LitCovid, medRxiv, and Google Scholar; assess study quality based on five criteria and report important findings. Where necessary, authors are contacted for further details on the content of their articles. Results: We include searches up until 20 December 2020. We included 110 relevant studies: 76 primary observational studies or reports, and 35 reviews (one cohort study also included a review) examining the potential role of orofecal transmission of SARS-CoV-2. Of the observational studies, 37 were done in China. A total of 48 studies (n=9,081 patients) reported single cases, case series or cohort data on individuals with COVID-19 diagnosis or their contacts and 46 (96%) detected binary RT-PCR with 535 out of 1358 samples positive for SARS-CoV-2 (average 39.4%). The results suggest a long duration of fecal shedding, often recorded after respiratory samples tested negative, and symptoms of gastrointestinal disease were reported in several studies. Twenty-nine studies reported finding SARS-CoV-2 RNA in wastewater, river water or toilet areas. Six studies attempted viral culture from COVID-19 patients’ fecal samples: culture was successful in 3 of 6 studies, and one study demonstrated invasion of the virus into intestinal epithelial cells. Conclusions: Varied observational and mechanistic evidence suggests SARS-CoV-2 can infect and be shed from the gastrointestinal tract, including some data demonstrating viral culture in fecal samples. To fully assess these risks, quantitative data on infectious virus in these settings and infectious dose are needed.